Halal certification from non-Muslim perspective: a case study of Starbucks Coffee / Annef Osyairi Osman, Nurul Hanizah Hamid Abdullah and Siti Fatimah Lailatul Qadrina Awang - Osman, Annef Osyairi; Hamid Abdullah, Nurul Hanizah; Awang, Siti Fatimah Lailatul Qadrina (2013)
This study aims to review the understanding of Halal certification from non-Muslim perspective. Halal certification at premises represents the understanding that foods is served according to Islamic Syariah law. It is our interest to see whether non-Muslim consumers are aware of the fundamental benefits that come with consuming Halal product and their insight on Halal certification. An international company, Starbucks Coffee was selected as our case studies which include five premises located around Kota Kinabalu area ; Centre Point, Suria Sabah, Warisan Square, City Mall and 1 Borneo Hypermall. 150 respondents from non-Muslim customers of Starbucks Coffee was selection using convenient sampling to answer the structured questionnaire regarding the study. Cross tabulation analysis was done to review the socio-demographic background and their level of understanding towards Halal certification. The analysis indicated that the respondent from tertiary education background have better understanding on Halal certification compared to the respondent with secondary background. The non-Muslim consumers understand that Halal certification signifies healthy food,purity, quality safety and hygienic of the product. The results also shows that the respondent age between 26 to 45 years old have better understanding on Halal certification compared to older generation.